Rare Complication of Takotsubo Cardiomyopathy: Ventricular Septal Perforation with Septal Dissection. Issue 3 (3rd December 2015) - Miyake, Keisuke; Funatsu, Toshihiro; Kondoh, Haruhiko; Taniguchi, Kazuhiro
Abstract: We describe a rare case of takotsubo cardiomyopathy complicated by acute ventricular septal perforation with ventricular septal dissection. The ventricular perforation was successfully closed by repairing the dissecting site with a bovine pericardial patch. doi: 10.1111/jocs.12676 (J Card Surg 2016;31:150–153)